Will Entrepreneurial Orientation Contribute to Entrepreneurial Success? - Oyeku, Oyedele M.; Oluseyi, Oduyoye; Karimu, F. A.; Akindoju, F. A.; Togunde, M. O.; Elemo, G. N. (Advances in Social Sciences Research Journal, 2020)
The purpose of this study is to examine the effect of entrepreneurial orientation on entrepreneurial success. The study population is the 9,450 small and medium enterprises (SMEs) who are registered members of the National Association of Small and Medium Enterprises (NASME), National Association of Small Scale Industrialists (NASSI) and Association of Small Business Owners in Nigeria (ASBON) in Lagos State. The study employs probability sampling technique and specifically, proportionate stratified random sampling method to select it samples from the sampling frame. Sample size of 381 determined using the formula developed by the National Education Association (1960) for sample size determination was used for this study. The study employed questionnaire as research instrument to collect primary data on the dependent variable (Entrepreneurial success) and independent variable (Entrepreneurial orientation). Entrepreneurial orientation measures are: Innovativeness, Proactiveness and Risk taking while measures for entrepreneurial success are: profitability, market share, net asset growth, sales growth and government policies. The questionnaire was pretested by a pilot study of 50 selected SMEs. Data from the pilot study was analyzed and based on the result, the questionnaire was slightly modified giving an overall Cronbach’s Alpha value of 0.853. The value of F (3,206) = 21.848, p <.05, shows that the combined effect of innovativeness, risk taking and pro-activeness was statistically significant in explaining changes in entrepreneurial success in Lagos State. The findings of the study also reveal that entrepreneurial pro-activeness had the highest influence on SMEs entrepreneurial success because the p value was 0.000 followed by risk taking with 0.007, and lastly innovativeness with a p value of 0.942. This finding may be of help to the owner/managers of SMEs to be more entrepreneurial oriented and developed competitive edge in order for them to survive the intensely competitive market environment.